ChatGPT in Aviation Education; A Bibliometric Mapping Visualized with Vosviewer - Kurnianto, Benny; Abdusshomad, Alwazir; Kalbuana, Nawang (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Since being released in November 2022, ChatGPT, a popular artificial-intelligence chatbot, has gained attention in almost all industry. It has been also rapidly evolving in education due to the rise of internet-based learning. This research aims to present a bibliometric mapping of ChatGPT in aviation education using mapping analysis with VOSviewer software. The research data was obtained using the Publish or Perish reference manager and was based on the keyword “ChatGPT in Aviation Education.” A total of 998 relevant articles which were indexed between 2017 and 2023 were found. The results indicate that the number of articles on ChatGPT in aviation education has been increasing since 2017 and 898 articles were published in 2023. This research is intended to provide a reference for researchers in selecting research themes related to ChatGPT in aviation education. From six clusters found, it visualized that numerous studies have already examined the relationship between ChatGPT and study, while the relationship between ChatGPT and flight has been less frequently analyzed. The relationship of those two items could be potential theme for advanced research.